2014
DOI: 10.1002/dta.1741
|View full text |Cite
|
Sign up to set email alerts
|

N,N‐dimethyl‐2‐phenylpropan‐1‐amine – new designer agent found in athlete urine and nutritional supplement

Abstract: Reports of new designer agents banned in sport being detected in supplements widely available for athletes are constantly emerging. The task of anti-doping laboratories is to control athletes for the presence of substances listed by the World Anti-Doping Agency (WADA) and those that are structurally/biologically similar to them. Recently, a new designer stimulant, N,N-dimethyl-2-phenylpropan-1-amine (NN-DMPPA), was detected by the WADA accredited anti-doping laboratory in Warsaw during routine anti-doping cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 16 publications
0
26
0
1
Order By: Relevance
“…In addition to the current study, several other investigators have found BMPEA in dietary supplements . FDA scientists analyzed 21 supplements labelled as containing Acacia rigidula purchased in 2012 and found that 9 of 21 (42.9%) contained BMPEA .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the current study, several other investigators have found BMPEA in dietary supplements . FDA scientists analyzed 21 supplements labelled as containing Acacia rigidula purchased in 2012 and found that 9 of 21 (42.9%) contained BMPEA .…”
Section: Resultsmentioning
confidence: 99%
“…Health Canada, however, has recently identified BMPEA in JetFuel Superburn which concurs with our analysis of the same brand . A European team has also detected BMPEA in two sports supplements, NO‐Shotgun and NOXPUMP . (NO‐Shotgun and NOXPUMP were not analyzed in the current study because they did not meet our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[102] The nutritional supplement product was purchased in Poland. [102] The nutritional supplement product was purchased in Poland.…”
Section: Synthetic Phenethylamines In Dietary Supplementsmentioning
confidence: 99%
“…[19] Both BMPEA and NN-DMPPA (N,N-dimethyl-2-phenylpropan-1-amine (13)) were detected in a work-out supplement called Noxpump, a product declared to be based upon extracts of Acacia rigidula as well. [20] Neither BMPEA nor DMPPA have been detected in extracts of Acacia rigidula. [21] Similarly, multiple stimulants were discovered in a supplement called Dexaprine.…”
mentioning
confidence: 98%